Genome-Wide Identification and Characterization of SPX Domain-Containing Members and Their Responses to Phosphate Deficiency in Brassica napus - Du, Hongyuan; Yang, Chang; Ding, Guangda; Shi, Lei; Xu, Fangsen (Frontiers in Plant Science, 2017)
The importance of SPX domain-encoding proteins to phosphate (Pi) homeostasis and signaling pathways has been well-documented in rice and Arabidopsis. However, global information and responses of SPX members to P stress in allotetraploid Brassica napus, one of the world’s major oil crops that is sensitive to P deficiency, remain undefined. We identified a total of 69 SPX domain-containing genes in the B. napus genome. Based on the domain organizations, these genes were classified into four distinct subfamilies—SPX (11), SPX-EXS (43), SPX-MFS (8) and SPX-RING (7)—that represented clear orthologous relationships to their family members in Arabidopsis. A cis-element analysis indicated that 2 ~ 4 P1BS elements were enriched in the promoter of SPX subfamily genes except BnaSPX4s. RNA-Seq analysis showed that BnaSPX genes were differentially expressed in response to Pi deficiency. Furthermore, quantitative real-time reverse transcription PCR revealed that nine SPX subfamily genes were significantly induced by Pi starvation and recovered rapidly after Pi refeeding. A functional analysis of two paralogous BnaSPX1 genes in transgenic Arabidopsis indicated their functional divergence during long-term evolution. This comprehensive study on the abundance, molecular characterization and responses to Pi deficiency of BnaSPX genes provides insights into the structural and functional diversities of these family members in B. napus and provides a solid foundation for future functional studies of BnaSPX genes.